QoS Performance Study of One Way Link Characteristics in an IEEE 802.16d TDD System - Maik Wodarz and James P. Taisie and Thomas C. Schmidt (IEEE, 2010)
WiMAX systems are beginning to spread as a wide-area wireless access technology that provides QoS support for future multimedia applications. Vendors have started to ship off-the-shelf hardware that addresses the market of broadband Internet coverage in sparsely populated areas. Facing a potentially large deployment of 802.16-based end-system connectivity, it is of vital interest to experimentally evaluate the capabilities of WiMAX systems in real-world setups. The main objective of our current paper is to quantify QoS performance of the one way wireless service flows in a 3.5 GHz band carrier utilizing the time division duplexing mode of the IEEE802.16 standard. We evaluate performance dependencies of the time division duplexing system on modulation and load, and show that the link latency is asymmetric.
Keywords: WiMAX; IEEE802.16; Latency; Jitter; QoS Measurements